Effectiveness of Reality Approach Group Counseling with WDEP Procedure to Reduce Students’ Academic Procrastination - Rahman, Khusnul Fatur; Pratiwi, Yasintha Sari (MOTIVA: JURNAL PSIKOLOGI, 2025)
This study aims to determine whether reality therapy group counseling, utilizing the WDEP (Wants, Doing, Evaluation, Planning) procedure, effectively reduces academic procrastination among high school students. A one‐group pretest‐posttest design was applied in this quantitative research. Data were gathered via purposive sampling from a population of 122 eleventh‐grade pupils at SMA Negeri 1 Loa Janan. 7 students exhibiting pronounced levels of academic procrastination, identified by the school counselor and homeroom teachers, were then selected to participate in the intervention. The researcher developed and validated the Academic Procrastination Scale to measure participants’ tendencies. Group counseling sessions incorporated WDEP steps alongside reality therapy techniques—statistical analysis employed paired‐sample t‐tests to compare pretest and posttest scores. Findings revealed a mean pretest score of 69.00, indicating high procrastination, which decreased to a mean posttest score of 41.28 after intervention. The paired‐sample t‐test yielded a p‐value of 0.001 (p < 0.05), confirming a statistically significant difference between initial and final measurements. Consequently, the null hypothesis (H0) was rejected, and the alternative hypothesis (Ha) was accepted, demonstrating that reality therapy group counseling combined with the WDEP procedure constitutes an effective strategy for reducing academic procrastination. These results contribute empirical support for integrating WDEP‐based reality therapy into school guidance and counseling programs. By providing a structured intervention framework, this study offers practitioners a practical, evidence‐based approach for addressing procrastination and enhancing student academic responsibility at the secondary education level.